Spatial Distribution Characteristics of Micronutrients and Their Deficiency Effect on the Root Morphology and Architecture in Citrus Rootstock - Gaofeng Zhou; Yiping Fu; Mei Yang; Yanhong Li; Jing Zhang (Plants)
Roots play essential roles in the acquisition of water and minerals from soils in higher plants. However, water or nutrient limitation can alter plant root morphology. To clarify the spatial distribution characteristics of essential nutrients in citrus roots and the influence mechanism of micronutrient deficiency on citrus root morphology and architecture, especially the effects on lateral root (LR) growth and development, two commonly used citrus rootstocks, trifoliate orange (Poncirus trifoliata L. Raf., Ptr) and red tangerine (Citrus reticulata Blanco, Cre), were employed here. The analysis of the mineral nutrient distribution characteristics in different root parts showed that, except for the P concentrations in Ptr, the last two LR levels (second and third LRs) had the highest macronutrient concentrations. All micronutrient concentrations in the second and third LRs of Ptr were higher than those of Cre, except for the Zn concentration in the second LR, which indicates that Ptr requires more micronutrients to maintain normal root system growth and development. Principal component analysis (PCA) showed that B and P were very close in terms of spatial distribution and that Mo, Mn, Cu, and Fe contributed significantly to PC1, while B, Cu, Mo, and Zn contributed significantly to PC2 in both rootstocks. These results suggest that micronutrients are major factors in citrus root growth and development. The analysis of root morphology under micronutrient deficiency showed that root growth was more significantly inhibited in Ptr and Cre under Fe deficiency (FeD) than under other micronutrient deficiencies, while Cre roots exhibited better performance than Ptr roots. From the perspective of micronutrient deficiency, FeD and B deficiency (BD) inhibited all root morphological traits in Ptr and Cre except the average root diameter, while Mn deficiency (MnD) and Zn deficiency (ZnD) had lesser impacts, as well as the morphology of the stem. The mineral nutrient concentrations in Ptr and Cre seedlings under micronutrient deficiency revealed that single micronutrient deficiencies affected both their own concentrations and the concentrations of other mineral nutrients, whether in the roots or in stems and leaves. Dynamic analysis of LR development revealed that there were no significant decreases in either the first or second LR number in Ptr seedlings under BD and ZnD stress. Moreover, the growth rates of first and second LRs in Ptr and Cre did not significantly decrease compared with the control under short-term (10 days) BD stress. Altogether, these results indicate that micronutrients play essential roles in citrus root growth and development. Moreover, citrus alters its root morphology and biological traits as a nutrient acquisition strategy to maintain maximal micronutrient acquisition and growth. The present work on the spatial distribution characteristics and micronutrient deficiency of citrus roots provides a theoretical basis for effective micronutrient fertilization and the diagnosis of micronutrient deficiency in citrus.